5x + 4 - 3x + 5 + 2x - 9 = 4x
6-3x = 5x-10x+10 6-3x = -5x+10 -3x+5x = 10-6 2x = 4 x = 2
58
3x2 + 5x + 2 is a quadratic expression that can be factored as follows: 3x2 + 5x + 2 = 3x2 + 3x + 2x + 2 = 3x(x + 1) + 2(x + 1) = (3x + 2)(x + 1)
15x2 + 58x + 48= 15x2 + 18x + 40x + 48= 3x(5x + 6) + 8(5x + 6)= (3x + 8)(5x + 6)
Two linear expressions with a sum of -5x plus 4 are ( -5x + 4 ) and ( 4 - 5x).
-1
3x+5x
5x+(6-3x)+8=5x+6-3x+8=2x+14 2x + 14
5x = 3x+1000+0 5x-3x = 1000 2x = 1000 x = 500
4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified
5x+8x+3x-2x = 14x
3x - 5x + x = -x
5x+3 = 3x+11 5x-3x = 11-3 2x = 8 x = 4
9x
5x^2 + 6x + 9 + (?) = -x^2 +3x + 3 (?) = -5x^2 -6x - 9 -x^2 +3x + 3 = -6x^2 -3x -6 Ans: -6x squared +3x -6
2x + 3x = 5x.